1985
DOI: 10.2337/diab.34.7.621
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Toxicity for Human Endothelial Cells in Culture: Delayed Replication, Disturbed Cell Cycle, and Accelerated Death

Abstract: Functional and anatomical abnormalities of endothelium may represent a pathway to the increased vascular permeability and accelerated atherosclerosis characteristic of diabetes. To identify whether and how hyperglycemia may compromise the endothelial barrier, we have employed an in vitro system of human endothelial cells obtained from umbilical veins and cultured in elevated glucose concentrations (20 mM). Under these conditions, the achievement of saturation density was substantially delayed, with cell counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(52 citation statements)
references
References 0 publications
7
43
2
Order By: Relevance
“…The effects of diabetes on the wound healing process are the impairment of cellular proliferation for most cell types (Sank et al, 1994;Hehenberger et al, 1998;Lerman et al, 2003), increased apoptosis of endothelial cells (Lorenzi et al, 1985;Baumgartner-Parzer et al, 1995;Darby et al, 1997), increased average blood glucose level (Williams and Pickup, 2001), impairment of blood vessel regrowth (Loots et al, 1998;Singer and Clark, 1999), inadequate flow through blood vessels (Singer and Clark, 1999;Greenhalgh, 2003) and decreased collagen deposition at the wound site (Black et al, 2003). Furthermore, it is likely that growth factor expression is altered (Shukla et al, 1998;Wetzler et al, 2000;Robson et al, 2001;Greenhalgh, 2003), and nitric oxide secretion (Bulgrin et al, 1995;Schaeffer et al, 1996;Schaeffer et al, 1997;Zykova et al, 2000) and macrophage removal to the lymph nodes may also be impaired (Bellingan et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…The effects of diabetes on the wound healing process are the impairment of cellular proliferation for most cell types (Sank et al, 1994;Hehenberger et al, 1998;Lerman et al, 2003), increased apoptosis of endothelial cells (Lorenzi et al, 1985;Baumgartner-Parzer et al, 1995;Darby et al, 1997), increased average blood glucose level (Williams and Pickup, 2001), impairment of blood vessel regrowth (Loots et al, 1998;Singer and Clark, 1999), inadequate flow through blood vessels (Singer and Clark, 1999;Greenhalgh, 2003) and decreased collagen deposition at the wound site (Black et al, 2003). Furthermore, it is likely that growth factor expression is altered (Shukla et al, 1998;Wetzler et al, 2000;Robson et al, 2001;Greenhalgh, 2003), and nitric oxide secretion (Bulgrin et al, 1995;Schaeffer et al, 1996;Schaeffer et al, 1997;Zykova et al, 2000) and macrophage removal to the lymph nodes may also be impaired (Bellingan et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies in type 1 DB rats (exhibiting hyperglycemia due to insulin deficiency) have shown increased hepatotoxic sensitivity to diverse structurally and mechanistically dissimilar hepatotoxicants due to inhibited tissue repair (Watkins et al, 1988;Mak and Ko, 1997;Wang et al, 2000a). In addition, in vitro studies have shown that hyperglycemia inhibits S-phase DNA synthesis (Lorenzi et al, 1985;Dajani et al, 1994;Rojas et al, 2003). Rao et al (1999) showed that high glucose concentration (28 mM) inhibited TA-stimulated S-phase due to perturbation in c-myc expression in human hepatoma (HuH7) cell line.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, more than 70 years ago, Cunningham [39, 40] showed that the peritoneal mesothelium of animals exposed to daily injections of 10% glucose during periods ranging between 6 and 14 days developed hypertrophic changes, namely large, multinucleated cells. This hypothesis about the effects of highly concentrated glucose and/ or glucose breakdown products inducing delayed cell cycle and/or cellular hypertrophy has been already proposed, based on observations made on nonmesothelial cell populations: skin fibroblasts [41], proximal tubule and glomerular mesangial cells [42, 43, 44], retinal microvascular pericytes and endothelial cells [45], and human umbilical vein endothelial cells [46, 47]. This perturbation of the cell cycle progression could be mediated, at least in part, by a block of activation of epidermal and other growth factors.…”
Section: Discussionmentioning
confidence: 99%